Resampling a carrion beetle fauna after 40 years (Coleoptera, Staphylinidae, Silphinae, and Leiodidae, Cholevinae) - Menno Schilthuizen; Teun van der Sterren; Isabel Kersten; Mike Groenhof; Henk van der Meulen; Leonie Wezendonk (Biodiversity Data Journal)
From 29 May until 5 June 1982, the first author placed baited pitfall traps to sample the Staphylinidae, Silphinae and Leiodidae, Cholevinae (Coleoptera) fauna in a mixed forest in the Netherlands. Exactly 40 years later (29 May until 5 June 2022), as a project on insect declines with high school students at a nearby school, a resampling was carried out.We report the silphine and cholevine specimens recorded both in 1982 and 2022. We found that total species richness and biomass had not noticeably changed, but there were some distinct appearances and disappearances of species. In addition, the species abundance distribution has become more skewed in favour of locally common species, such as Sciodrepoides watsoni and Fissocatops westi. We discuss our results in the context of insect declines worldwide.